Native Customary Rights Over Land in Sarawak - Adam, Francis Johen (Journal of Malaysian and Comparative Law, 2019)
The purpose of this paper is to explain the law relating to native customary rights in respect of land in Sarawak, with reference to relevant provisions in the Sarawak Land Code, hereinafter referred to as the Land Code or the Code.